الكفاءة في عقد الزواج وفقا لقانون الأحوال الشخصيّة الأردني المؤقّت "دراسة مقارنة - طلال المومني, بشار (جامعة الوادي University of Eloued, 2012)
يعالج هذا البحث: موضوع الكفاءة في عقد الزواج, تنظيمه القانوني والفقهي, والصفات المعتبرة في الكفاءة. وكانت مسالة الكفاءة ولا تزال موضع نقاش ومحلّ خلاف قانوني وفقهي بين التضييق والتوسيع في الصفات المعتبرة في الكفاءة. وختمنا ببعض النتائج وأبدينا بعض المقترحات، كمحاولة لإعادة النظر في النصوص القانونية الحالية وتوحيدها. وأوصى الباحث: بعدم اعتماد معيار حصري لعناصر الكفاءة بين الزوجين نظرا لاختلاف الزمان والمكان، وأن يكون المعيار متناسبا مع العصر الذي يوضع فيه ويكون من شأنه تحقيق التوافق والانسجام وعدم تسرّع المقبلين على الزواج في الاختيار, وإجراء الفحوصات الضرورية قبل الزواج, والتركيز على الدين، وعدم التفاوت الكبير في العمر، ومستوى التعليم, والمقدرة على الإنفاق وليس الغنى كعناصر مهمّة وأساسية في الزواج. Abstract: This research deals with the subject of parity in the marriage contract; its legal and jurisprudential (Fiqhi) regulation as well as the legal considerations of the parity. The issue of parity has been and still under legal and jurisprudential argument between narrowing and widening the legal considerations of the parity. We concluded with some results and set some suggestions as a try to re-review and unify the current legal provisions. The researcher recommended the following: it’s not preferable to depend on the restrictive standards of parity between the spouses due to the differences in time and place. The standards should be suitable to the era in which it is issued to achieve harmony and agreement. In addition, it is preferable not to make quick decisions concerning the choosing of the future spouse as well as conducting the necessary medical examinations before marriage. Moreover, it’s a must to concentrate on the religion doctrines; the difference in age and education between the spouses should not be so wide. And finally, the ability to meet the life requirements; it is not supposed to mean that spouse should be rich. All the above recommendation may help in shaping the main elements for a good marriage.
Keywords: الكفاءة؛ العقد؛ الزواج؛ التنظيم القانوني؛ التنظيم الفقهي؛ قانون الأحوال الشخصيّة؛ القانون المدني